A Study on Benefits Applications and Problems in Multi-Tenancy Techniques in Cloud Computing Models: Exploring the Benefits and Challenges of Secure Multi-Tenancy in Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Cloud Computing is the most trending Information Technology computational model. This environment is enabled with an Internet to provide computing resources comprised of software, servers, Storages and applications that can be accessed by any type of client. Cloud computing is the fundamental model to provide the services like Infrastructure as a Service, Platform as a Service and Software as a Service. Majority of these services are offered based on pay per use lease style investment with very low or no startup costs to purchase all hardware or software components. The feature provides economic benefits to both users and service providers since it reduces the management cost and thus lowers the subscription price. Many users are, however, reluctant to subscribe to cloud computing services due to security concerns. To enable deployment of cloud computing, we need to advance new techniques like secure multi-tenancy, resource isolation need to be advanced further.